Perceptions of women and partners on labor and birth positions: A meta‐synthesis. Issue 1 (9th July 2021) - Shorey, Shefaly; Chan, Valerie; Lalor, Joan Gabrielle
Abstract: Background: The risks and benefits of different birthing positions are commonly studied, but both paternal and maternal preferences and experiences of different birth positions are not examined. Therefore, this systematic review aims to explore the perceptions of women and their partners on birthing positions during the first and second stage of labor, so that maternity health care practitioners can provide better quality patient‐centered care. Methods: Six databases were searched from each database's inception through November 2020. Qualitative or mixed‐methods studies exploring perceptions of women and/or their partners on birthing positions were included in the review. Key information and findings of the studies were extracted; qualitative data were meta‐summarized, then meta‐synthesized using thematic analysis. Results: Seven studies were included, and four themes emerged: (a) Influences on choice and preference; (b) mixed experiences from "pain" to "more in control"; (c) impact on postpartum health; and (d) ways to empower couples in their choice. Conclusions: Women's preferences for birthing positions were influenced by a myriad of personal and socio‐cultural beliefs and traditions. Findings suggest a need for health care practitioners to build better rapport and provide more culturally relevant informational support to both women and their birthing partners, so they are better able to make informed decisions on their preferred birthing position.